Stimulation of Human Innate Immune Defenses by Bacteria in vitro - Manal Badi Salih AL-tmemi (مجلة علوم ذي قار, 2019)
The microflora is essential for immune education and amplification of lymphoid effector cells, mainly at the mucosal level. It is well documented that the efficacy of the mucosal immune system can be significantly impaired in germ-free animals. In this study the bacteria used as antigens (mitogen) to the stimulation of human immune cells in vitro. Gram-positive Streptococci spp and gram-negative Escherichia coli was investigated. The stimulation of human peripheral blood mononuclear cells by the various bacterial strains induced a differential cytokine pattern. Streptococci and E. coli significantly (P ≤ 0.001) induced gamma interferon (IFN- ) and interleukin-12 (IL-12). All bacteria mediated the proliferation of human peripheral blood mononuclear cells. Proliferate activity of lymphocytes was observed when mitogens were added. The MTT is employed to assess the response of lymphocytes to a mitogen. Bacteria and PHA was effective in inducing the MTT index of lymphocytes. Therefore, PHA, gram-positive bacteria, and gram-negative bacteria showed a high significant (P ≤ 0.001) increased percentage of MTT index (96.4, 88.2 and 74.7 %, respectively) as compared to control subjects (42.5%) with no treatment.